Meta-analysis of effects of exclusive breastfeeding on infant gut microbiota across populations - Nhan T. Ho (Nature Portfolio, 2018)
Studies on the effects of breastfeeding on the infant gut microbiota have provided inconsistent results. Here, Ho et al. perform a meta-analysis of seven studies across different populations, supporting that exclusive breastfeeding is associated with short-term and long-term alterations in the infant gut microbiota.